Directing Group‐Promoted Inert C−O Bond Activation Using Versatile Boronic Acid as a Coupling Agent. Issue 71 (19th November 2020) - Ambre, Ram; Wang, Ting‐Hsuan; Xian, Anmei; Chen, Yu‐Shiuan; Liang, Yu‐Fu; Jurca, Titel; Zhao, Lili; Ong, Tiow‐Gan
Abstract: A simple Ni(cod)2 and carbene mediated strategy facilitates the efficient catalytic cross‐coupling of methoxyarenes with a variety of organoboron reagents. Directing groups facilitate the activation of inert C−O bonds in under‐utilized aryl methyl ethers enabling their adaptation for C−C cross‐coupling reactions as less toxic surrogates to the ubiquitous haloarenes. The method reported enables C−C cross‐coupling with readily available and economical arylboronic acid reagents, which is unprecedented, and compares well with other organoboron reagents with similarly high reactivity. Extension to directing group assisted chemo‐selective C−O bond cleavage, and further application towards the synthesis of novel bifunctionalized biaryls is reported. Key to the success of this protocol is the use of directing groups proximal to the reaction center to facilitate the activation of the inert C−OMe bond. Abstract : DG assisted : Directing group assisted nickel catalyzed C−OMe bond activation for C−C cross‐coupling is reported. C−O activation of rarely explored methyl ethers and C−C cross‐coupling with a wide range of readily available boronic acid reagents is achieved. The strategy could be further extended to afford novel bifunctionalized biaryls.